Can a Constitution be tacitly amended? Comparative analysis to the problem of the tacit amendment to the Constitution and the normative hierarchy of Traties in Chile - Lagos Torres, Alejandro (Derecho Público Iberoamericano, 2022)
The classic dilemma of the hierarchy of international treaties within the Chilean legal system is analyzed, leaving the arguments based on the semantic and literalness of the texts, now addressing the matter from a modern perspective focused on the problems caused by the “tacit” constitutional amendments. The theory of the constitutional block in comparative law is studied, with a special mention to the phenomenon of European Union law, so that experience helps us to resolve this controversy.